2019
DOI: 10.4236/jct.2019.109064
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neutrophil to Lymphocytic Ratio (NLR) as a Predictor of Treatment Outcomes in Rectal Carcinomas: A Retrospective Cohort Study

Abstract: Background and aim: The prognostic role of neutrophil to lymphocyte ratio (NLR) has been shown in many solid tumors included in a recent meta-analysis of one hundred studies. We aimed to evaluate the prognostic value of neutrophil to lymphocyte ratio in treatment outcomes; response and survival of patients with different stages of rectal cancers. Patients and methods: All patients with pathologically confirmed cancer rectum presented to our department during the period from January 2012 to the end of 2014 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…High NLR and MLR values indicate an unjustified immune reaction, which diminishes the predictability of anti-tumor resolution. As systemic inflammation leads to changes in the circulatory blood leukocytes, it is suggested that NLR and MLR values can be considered as an indicator for forecasting malignancy invasion and severity [38]. The results of the current study revealed a remarkable, significant decrease in NLR, MLR, and PLR values in the TW extract treated mice.…”
Section: Discussionsupporting
confidence: 48%
“…High NLR and MLR values indicate an unjustified immune reaction, which diminishes the predictability of anti-tumor resolution. As systemic inflammation leads to changes in the circulatory blood leukocytes, it is suggested that NLR and MLR values can be considered as an indicator for forecasting malignancy invasion and severity [38]. The results of the current study revealed a remarkable, significant decrease in NLR, MLR, and PLR values in the TW extract treated mice.…”
Section: Discussionsupporting
confidence: 48%